2016
DOI: 10.1038/tp.2016.160
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressive and BDNF effects of enriched environment treatment across ages in mice lacking BDNF expression through promoter IV

Abstract: Reduced promoter IV-driven expression of brain-derived neurotrophic factor (BDNF) is implicated in stress and major depression. We previously reported that defective promoter IV (KIV) caused depression-like behavior in young adult mice, which was reversed more effectively by enriched environment treatment (EET) than antidepressants. The effects of promoter IV-BDNF deficiency and EET over the life stages remain unknown. Since early-life development (ED) involves dynamic epigenetic processes, we hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 92 publications
(171 reference statements)
3
44
3
Order By: Relevance
“…In particular, EE protects from dendritic atrophy as well as reductions in neurogenesis and neurotrophin expression following adult stress (Hutchinson et al, 2012; Shilpa et al, 2017; Veena et al, 2009; Vega‐Rivera et al, 2016). Previous studies have also shown that exposure to EE during a critical developmental period (0–2 postnatal months), is more effective at increasing BDNF levels (Jha et al, 2016). In this respect, our BDNF increases are in line with existing evidence, indicating a beneficial role of post‐weaning EE (PND23‐65) against MS‐associated decreases in BDNF expression.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, EE protects from dendritic atrophy as well as reductions in neurogenesis and neurotrophin expression following adult stress (Hutchinson et al, 2012; Shilpa et al, 2017; Veena et al, 2009; Vega‐Rivera et al, 2016). Previous studies have also shown that exposure to EE during a critical developmental period (0–2 postnatal months), is more effective at increasing BDNF levels (Jha et al, 2016). In this respect, our BDNF increases are in line with existing evidence, indicating a beneficial role of post‐weaning EE (PND23‐65) against MS‐associated decreases in BDNF expression.…”
Section: Discussionmentioning
confidence: 96%
“…We found that EET effects in increasing exploratory activity and anti‐despair behavior were largest and long‐lasting when EET was provided during ED, particularly in promoter IV‐BDNF‐deficient mice . BDNF protein induction in the hippocampus and frontal cortex was also the largest after early‐life EET, while the EET effects were limited in old‐adult (OA) mice . These results led to our hypothesis that EET during ED provides maximum and lasting effects in antidepressive behavior and BDNF induction.…”
Section: Introductionmentioning
confidence: 89%
“…We recently examined EET effects across 3 distinctive life stages in mice: early‐life development (ED), young‐adulthood and old‐adulthood. We found that EET effects in increasing exploratory activity and anti‐despair behavior were largest and long‐lasting when EET was provided during ED, particularly in promoter IV‐BDNF‐deficient mice . BDNF protein induction in the hippocampus and frontal cortex was also the largest after early‐life EET, while the EET effects were limited in old‐adult (OA) mice .…”
Section: Introductionmentioning
confidence: 97%
“…Early EE studies demonstrated widespread effects on numerous CNS cell types and under varied physiological conditions in both small and large mammals [84,85,86,87,88]. Differential rearing in infant rhesus monkey shows that animals raised in larger groups demonstrate expansion of the CC and sustained improvement in cognitive performance versus age-matched, individually raised controls [89].…”
Section: Environmentally Influenced Changes In Myelin Structure and Fmentioning
confidence: 99%